Staying silent or speaking up: reactions to racialization affecting Muslims in Madrid - Lems, Johanna M. (Ethnic and racial studies, 2021)
This study examines the reactions of Muslims in Madrid to racialized interpellations in their everyday lives. Considering that political subject positions are formed at the intersection of interpellations from different discursive contexts, this study aims to grasp how Muslims living in Madrid discursively perceive and interpret the existence of options to raise their voice and be heard. How do they consider being addressed and in which spaces does this occur? Who makes the interpellation and from which position? What are their reactions? The audio and transcript material on which this research is based was obtained from six discussion groups representing Muslim populations in Madrid, held in October 2016. The analysis shows that Muslims in Madrid feel discriminated against in their daily lives, but have limited possibilities to speak up and be heard.